Distribution and laterality of concha bullosa in patients with different cranial skeletal types: a retrospective analysis among cases with concha bullosa - Farhad Ghorbani; Ali Modaberi; Nasim Morshedian; Ali Gorgin; Maryam Paknahad (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Objective Concha bullosa, a common anatomical variation characterized by air-filled cavities in the turbinate bones, can influence sinonasal function and surgical planning. This study aims to evaluate the distribution, laterality, and cranial skeletal type associations of concha bullosa (CB) among patients with confirmed CB findings on computed tomography (CT) scans. Methods A retrospective cohort study was conducted on 774 patients who underwent cranial and facial CT scans between March 2023 and March 2024. Patients were classified into mesocephalic, brachycephalic, and dolichocephalic groups based on the cephalic index. The distribution and laterality of concha bullosa were assessed using CT scans, and statistical analyses were performed using the Chi-square test, with a significance level set at P < 0.05. Results Among CB-positive patients, left-sided concha bullosa was most common (49.48%), followed by right-sided (31.91%) and bilateral (18.6%) involvement. Mesocephalic individuals constituted the largest proportion of CB-positive cases (55.56%), followed by dolichocephalic (22.86%) and brachycephalic (21.57%) individuals. A significant gender difference was observed in the mesocephalic (P = 0.001) and brachycephalic (P = 0.013) groups, with males exhibiting a higher prevalence of right-sided and bilateral concha bullosa. Conclusion Concha bullosa distribution varies significantly among cranial skeletal types among CB-positive patients, with mesocephalic individuals exhibiting the highest overall prevalence. Our findings underscore the influence of cranial morphology on the presentation of CB. This insight may enhance radiological evaluation and individualized surgical planning in CB-positive patients.